Ultraviolet-ray treatment of polysulfone membranes on the O2/N2 and CO2/CH4 separation performance - Sutthisa Konruang (2018)
© 2015 Wiley Periodicals, Inc. UV irradiation on polysulfone (PSF) membranes was studied to improve their gas-separation properties. Membranes with 19-25% PSF contents were prepared by the phase-inversion method, and the membrane surface was modified with UV rays with a wavelength of 312 nm and a power of 360 μw/cm2. Measurements of gas permeation were conducted with pure carbon dioxide (CO2), methane (CH4), oxygen (O2), and nitrogen (N2) gases under 3-8 bar pressure at 25°C. Fourier transform infrared spectrometry revealed that the polar functional groups of hydroxyl and carbonyl were introduced by UV irradiation. The water contact angle of the treated membrane was reduced from 70-75° to 10-12° after 12 h of UV exposure. Scanning electron microscopy observation showed that the dense skin layer increased as the polymer concentration increased. After UV treatment, the permeation of O2 decreased from 0.4-3.4 to 0.2-2.3 m3 m-2 h-1 bar-1, whereas that of N2, CO2, and CH4 increased for all of the pressures used from 0.1-1.7 m3 m-2 h-1 bar-1 to about 0.1-3.4 m3 m-2 h-1 bar-1; this depended on the applied pressure and the PSF content. As a result, the selectivity ratio of O2/N2 decreased from 1.9-7.8 to 0.6-1.5, whereas that of CO2/CH4 increased from 0.9-2.6 to 1.1-6.1. Moreover, the O2/N2 and CO2/CH4 of the untreated and the treated membranes decreased with increasing pressure and increased with increasing polymer concentration.